A novel 86-bp indel of the motilin receptor gene is significantly associated with growth and carcass traits in Gushi-Anka F2 reciprocal cross chickens. Issue 6 (2nd November 2019) - Liu, D.; Han, R.; Wang, X.; Li, W.; Tang, S.; Li, W.; Wang, Y.; Jiang, R.; Yan, F.; Wang, C.; Liu, X.; Kang, X.; et al.
ABSTRACT: 1. A previous whole-genome association analysis has identified the motilin receptor gene ( MLNR ), which regulates gastrointestinal motility and gastric emptying, as a candidate gene related to chicken growth. 2. MLNR mRNA was expressed in all tissues tested, and the expression level in digestive tissues was greater than in other tissues. Expression levels in the pancreas, duodenum and glandular stomach at day old and one, two and three weeks of age indicated a possible correlation with the digestive system. This suggested that the MLNR gene plays a central role in gastrointestinal tract function and affects the growth and development of chickens. Moreover, there was a significant difference in expression in the glandular stomach tissue between Ross 308 and Gushi chickens at six weeks of age. 3. Re-sequencing revealed an 86-bp insertion/deletion polymorphism in the downstream region of the MLNR gene. The mutation locus was genotyped in 2, 261 individuals from nine different chicken breeds. MLNR expression levels in the glandular stomach of chickens with DD genotypes were greater than those in chickens with the ID and II genotypes. The DD genotype was the most dominant genotype in commercial broiler's (Ross 308 and Arbor Acres broilers), and the D allele frequency in these breeds exceeded 91%. The deletion mutation tended towards fixation in commercial broilers. 4. Association with growth and carcass traits analysed in a Gushi-Anka F2 intercrossed population, showed that the DD genotype was significantly associated with the greatest growth and carcass trait values, whereas values associated with the II genotype were the lowest in the F2 reciprocal cross chickens. 5. The results suggest that the mutation is strongly associated with growth related traits and it is likely to be useful for marker-assisted selection of chickens.